2001
DOI: 10.1002/ijc.1455
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid capture-II and LCR-E7 PCR assays for HPV typing in cervical cytologic samples

Abstract: As part of an ongoing cohort study in the Hokuriku region of Japan, cervical cell samples from histologically confirmed normal (n ‫؍‬ 114) or abnormal (n ‫؍‬ 286) women were examined for the presence of HPV DNA using a second-generation hybrid capture assay (HCA-II) and LCR-E7 PCR. HCA-II detected low-risk (HPV-6, -11, -42, 43 and -44) and high-risk (HPV-16, -18, -31, -33, -35, -39, -45, -51, -52, -56, -58, -59 and -68) HPV types, while LCR-E7 PCR detected an additional 7 HPV types and some uncharacterized typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
5
31
1
2
Order By: Relevance
“…High-risk oncogenic HPV types has been found to be the main risk factor for cervical neoplasia [9]; it is also a good predictor of subsequent high-grade lesions in young women [11,12]. Corroborating this proposal, HCA II results were strongly associated with the likelihood of SIL, since we observed that 87% of the patients presenting SIL were also infected by HPV, with a positive trend relating high-risk HPV to cervical transformation (p<0.00001).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…High-risk oncogenic HPV types has been found to be the main risk factor for cervical neoplasia [9]; it is also a good predictor of subsequent high-grade lesions in young women [11,12]. Corroborating this proposal, HCA II results were strongly associated with the likelihood of SIL, since we observed that 87% of the patients presenting SIL were also infected by HPV, with a positive trend relating high-risk HPV to cervical transformation (p<0.00001).…”
Section: Discussionsupporting
confidence: 69%
“…These cases could be latent infections or incipient cervical lesions [13], characterizing a low level of HPV gene replication [10]. However, it also might be due to either DNA testing errors or errors in the cytological diagnosis [9,11]. Viral testing could help to focus on a group of patients with a high risk of developing lesions in the near future, especially in Brazil, due to the high frequency of cervical cancer [15].…”
Section: Retrospective Analysis Of the Patients Samples (N)mentioning
confidence: 99%
“…Other studies have also shown that the amount of HPV DNA is a useful predictor of progression to cervical carcinoma, and concluded that the risk of cancer increased correspondingly [15]. But there have been conflicting reports about correlation between viral load and risk of SIL [16]. Thus, the quantitative aspects of the hybrid capture test merit further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of HC-II is its ability to estimate viral genome copy number from the magnitude of the RLU value obtained. 14,15 As the RLU value reflects the activity of HPV, it may be closely associated with the progression of papilloma. 15 In fact, our HC-II data showed that the RLU values in recurrent and re-recurrent papilloma specimens were 25 times and 115 times higher, respectively, than in the primary specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation hybrid capture (HC-II) assay is a non-radioactive, reproducible, relatively rapid liquid hybridization assay, with a sensitivity similar to that of PCR. 13,14 It is based on the measurement of relative light units (RLUs) as a semiquantitative index of the amount of HPV DNA. 15 Some previous studies have shown that the RLU level is correlated positively with disease severity.…”
Section: Introductionmentioning
confidence: 99%